EMPOWERING MOTHERS IN THE PROCESSING OF LOCAL CLARIAS NUGGETS DIVERIFIED FOODS INTO HEALTHY MPASI FOR STUNTING UNDER-FIVES IN THE WORKING AREA OF KASEMEN PUSKESMAS IN 2023 - Rahmawati, Dewi; Sundary Lintang, Santi; Yulidar, Elfina; Ernawati, Eka; Alifiani, Herna; Atma Sella, Marlina; Febriyanti, Rizka; Fadilah, Eli (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Community service in the form of health education activities for the target community through 2 activities in the form of providing education about stunting and appropriate feeding patterns for toddlers based on the contents of my plate, and the second stage is demonstrating the steps for cooking one of the fish-based complementary food menus (catfish) become a food that is often in demand by children in the form of processed "nuggets". the activities were carried out face-to-face on February 13 and February 21 2023 with the target of mothers who have toddlers who are stunted. The purpose of this activity is to add information and strengthen mother's knowledge in understanding stunting, prevention and how to provide proper feeding patterns to children. In addition, it equips mothers with skills and motivates them to process healthy fishbased food into delicious, healthy and of course nutritious catfish nuggets in a way that is easy to do through cooking classes. This was done by looking at the phenomenon of the problem from the results of the research conducted which found field data that the incidence of stunting in children in Margaluyu Village, the Working Area of the Kasemen Health Center has increased every year. This activity was attended by 17 mothers and toddlers in one of the village cadres' houses. The stages of the activities carried out in the education class were in the form of giving questionnaires to explore the mother's knowledge and feeding patterns (pre-test), then measuring the growth curve with a microtoise and checking the development of toddlers using the KPSP. Followed by giving material for 25 minutes and a question and answer process and evaluation. The second stage was carried out 1 week later with a series of activities in the form of a cooking class for processed MPASI side dishes in the form of catfish nuggets by conducting direct demonstrations to mothers with stunting toddlers who previously carried out a post test first with the same questionnaire. The evaluation stage is by conducting follow-up through village cadres regarding knowledge and patterns of feeding to mothers whether there have been changes, mothers' ability to make processed catfish nuggets independently at their respective homes and given them routinely to children. The final stage is to carry out follow-up which is still ongoing regarding the improvement of the child's growth curve measured for 3 months.